COMPARISON OF GENERAL PATIENT SATISFACTION LEVEL WITH BPJS PATIENTS IN MAIN INSTALLATION SERVICES GRAND LUBUK PAKAM HOSPITAL - Keleng Ate Ginting; Fina Aulia (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Consumer satisfaction with the services received can be measured by comparing expectations with the quality of service they receive. If the consumer expects service at a certain level and the service he receives is higher than he expected then the consumer is very satisfied. The research method used in this study is a study using a cross sectional approach that aims to see a comparison of the level of satisfaction of general patients with BPJS patients in outpatient installation services. Independent variables in this study are the satisfaction of general patients and BPJS and for Dependent Variables in this study is a service at the Outpatient Installation at Grandmed Lubuk Pakam Hospital. The research subjects in this study were all BPJS patients and outpatient generals at Grandmed Lubuk Pakam Hospital which numbered 30 respondents. The data collection used in this study was by questionnaires and interviews. Primary data collected.